2021
DOI: 10.3390/en14092360
|View full text |Cite
|
Sign up to set email alerts
|

The Issues of the Air-Fuel Ratio in Exhaust Emissions Tests Carried out on a Chassis Dynamometer

Abstract: Vehicle exhaust emission tests use exhaust sampling systems that dilute the exhaust gas with ambient air. The dilution factor DF is calculated assuming that the combustion is complete, and that the engine is operated at a stoichiometric air-fuel ratio (AFR). These assumptions are not always met. This is especially true for diesel engines. This article discusses the tests to find out what the average lambda (λ) over the ARTEMIS, WLTC and NEDC driving cycles is and how this affects the result of the emission mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Grzelak et al [33] (2021) indicated that the use of various calculation methods may result in approximately 7% underestimation of road CO 2 emission results when testing LPG-powered vehicles. This was also confirmed by Gis et al [34] (2021), indicating that the interchangeable treatment of indicators (dilution ratio and dilution factor) in mathematical calculations of exhaust emissions affected the measurement error of CO 2 concentration by 0.4%, CO by a maximum of 4%, and NO x by 1%.…”
Section: Literature Reviewsupporting
confidence: 66%
“…Grzelak et al [33] (2021) indicated that the use of various calculation methods may result in approximately 7% underestimation of road CO 2 emission results when testing LPG-powered vehicles. This was also confirmed by Gis et al [34] (2021), indicating that the interchangeable treatment of indicators (dilution ratio and dilution factor) in mathematical calculations of exhaust emissions affected the measurement error of CO 2 concentration by 0.4%, CO by a maximum of 4%, and NO x by 1%.…”
Section: Literature Reviewsupporting
confidence: 66%